آليات تحقيق التنمية المستدامة في إفريقيا من منظور أجندة 2063 - حفري آمال (université d'eloud, 2025)
الملخص: نتيجة للأوضاع الصّعبة التي تعيشها القارة في مختلف المجالات، شرع قادة الدول الإفريقيّة في صياغة خطّة طموحة وشاملةتمثّلت في أجندة الاتحاد الإفريقي 2063،والتي تهدف إلى تحقيق التنمية المستدامة ودفعإفريقيانحو مرحلة جديدة تعزّز مكانتها على السّاحة الدوليّة. وعليه، تهدف الدراسة إلى تقديم إطار تحليلي فيم يتعلق بالآليات المسؤولة عن تنفيذ بنود أجندة 2063 لضمان تحقيق التنمية المستدامة في القارة، ولذلك فهي تعمل على تحقيق ثلاثة أهداف مركزيّة؛ يتمثّل الأوّل في معرفة أهم الأسباب الكامنة وراء صياغة أجندة 2063 والإحاطة بمضمونها،بينما يركّز الثاني على دراسة الآليات التنفيذيّة، مع عرض أهم ومختلف الاستراتيجيّات والتدابير المعتمدة لتحقيق أهداف التنمية المستدامة على مستويات مختلفة، أمّا الهدف الأخير،فيتناول تقييم أداء هذه الآليات في تنفيذ الأجندة، وذلك لمعرفة مدى نجاحهافي تحقيق أهدافها، مع تسليط الضوء على أبرز التحديات التي واجهتها. وقد خلصت الدراسة إلى أنّ قدرة وفعاليّة الآليّات المختلفة على تنفيذ أهداف التنمية المستدامة وفقا لأجندة 2063 كانت محدودة، مع وجود تفاوت في مستويات الأداء. Abstract : As a result of the challenging conditions experienced across various sectors in the African continent, African leaders initiated the formulation of an ambitious and comprehensive plan: The African Union Agenda 2063. This agenda aims to achieve sustainable development and to lead Africa into a new phase that enhances its position on the international stage. Accordingly, this study seeks to provide an analytic framework regarding the mechanisms responsible for implementing the provisions Agenda 2063 in order to ensure the realization of sustainable development across the continent. The study pursues three main objectives: the first is to identify the key drivers behind the formulation of Agenda 2063 and to explore its content; the second focuses on examining the implementation mechanisms, including a presentation of the major strategies and measures adopted to achieve the sustainable development goals at various levels, and the third aims to assess the performance of these mechanisms in implementing the agenda, in order to determine the extent of their success and to highlight the main challenges they have encountered. The study concludes that the capacity and effectiveness of various mechanisms in implementing the sustainable development goals, as outlined in Agenda 2063, have been limited, with noticeable disparities in performance.
أطروحة دكتوراء
Keywords: التنمية المستدامة; إفريقيا; أجندة الإتحاد الإفريقي; 2063